Osteology of the sauropodomorph dinosaur Jaklapallisaurus asymmetricus from the Late Triassic of central India - Ezcurra, Martin Daniel (2023)
The Gondwana formations exposed in the Pranhita-Godavari Valley ofcentral India include Middle Triassic to Lower Jurassic continentaldeposits that provide essential information about the tetrapod assemblagesof that time, documenting some of the oldest known dinosaursand the first faunas numerically dominated by this group. The UpperMaleri Formation of the Pranhita-Godavari Basin preserves an earlymiddleNorian dinosaur assemblage that provides information about theearly evolutionary history of this group in central-south Gondwana. Thisassemblage comprises sauropodomorph dinosaurs and an herrerasaurian,including two nominal species. Here, we describe in detail the anatomyof one of those early dinosaurs, the bagualosaurian sauropodomorphJaklapallisaurus asymmetricus. The new anatomical information is usedto investigate the position of the species in an updated quantitative phylogeneticanalysis focused on early sauropodomorphs. The analysis recoveredJaklapallisaurus asymmetricus as a member of Unaysauridae, at thebase of Plateosauria, together with Macrocollum itaquii and Unaysaurustolentinoi from the early Norian of southern Brazil. This phylogeneticresult indicates that the dispersal of early plateosaurian sauropodomorphsbetween the Southern Hemisphere and what nowadays is Europe wouldhave occurred shortly after Ischigualastian times because of the extensionof their ghost lineage. Thus, the presence of early plateosaurians in theearly Norian of South America and India reduces a previously inferreddiachrony between the biogeographic dispersals of theropods and sauropodomorphsduring post-Ischigualastian times.